MATH SOLVE

3 months ago

Q:
# 3x + 2y = 7 x - y + 3 = 0 What is the resulting equation? 3x - y - 3 + 2y = 7 3(y - 3) + 2y = 7 3y - 3 + 2y = 7

Accepted Solution

A:

I'm not comfortable with having two " = " signs in the same equation, at least not in this situation.

You apparently meant to type in the system of linear equations

3x + 2y = 7

x - y = -3

but did not separate 3x + 2y = 7 and x - y = -3 with a comma as required.

I will assume that you meant to share:

3x + 2y = 7

x - y = -3 This system of linear equations has a solution, but there

will be no "resulting equation."

Please ensure that you have copied down this problem exactly as it was originally presented. Explain what we are to do with

3x + 2y = 7 x - y + 3 = 0: How do we interpret this?

You apparently meant to type in the system of linear equations

3x + 2y = 7

x - y = -3

but did not separate 3x + 2y = 7 and x - y = -3 with a comma as required.

I will assume that you meant to share:

3x + 2y = 7

x - y = -3 This system of linear equations has a solution, but there

will be no "resulting equation."

Please ensure that you have copied down this problem exactly as it was originally presented. Explain what we are to do with

3x + 2y = 7 x - y + 3 = 0: How do we interpret this?